Parents with periodontitis impact the subgingival colonization of their offspring - Monteiro, Mabelle Freitas (Sci Rep, 2021)
Early acquisition of a pathogenic microbiota and the presence of dysbiosis in childhood is associated with susceptibility to and the familial aggregation of periodontitis. This longitudinal interventional case–control study aimed to evaluate the impact of parental periodontal disease on the acquisition of oral pathogens in their offspring. Subgingival plaque and clinical periodontal metrics were collected from 18 parents with a history of generalized aggressive periodontitis and their children (6–12 years of age), and 18 periodontally healthy parents and their parents at baseline and following professional oral prophylaxis. 16S rRNA amplicon sequencing revealed that parents were the primary source of the child's microbiome, affecting their microbial acquisition and diversity. Children of periodontitis parents were preferentially colonized by Filifactor alocis, Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Streptococcus parasanguinis, Fusobacterium nucleatum and several species belonging to the genus Selenomonas even in the absence of periodontitis, and these species controlled inter-bacterial interactions. These pathogens also emerged as robust discriminators of the microbial signatures of children of parents with periodontitis. Plaque control did not modulate this pathogenic pattern, attesting to the microbiome's resistance to change once it has been established. This study highlights the critical role played by parental disease in microbial colonization patterns in their offspring and the early acquisition of periodontitis-related species and underscores the need for greater surveillance and preventive measures in families of periodontitis patients.